Assessing the usefulness of frameworks for sub-categorizing faith-based organizations: World Vision as a case study. (February 2016) - Mitchell, Bob
Faith-based organizations (FBOs) make up one of the largest cohorts of organizations providing international development work around the globe. The extraordinary heterogeneous nature of FBOs is bewildering, and typologies and other methods have been developed to try and sub-categorize them or to distil their defining characteristics. This article looks at how useful some of those attempts are for analytical purposes. Taking data from a detailed case study of eight World Vision offices around the globe, it was possible to go back and test the robustness of some of these methods. Typologies were inadequate because they forced an approximation or tried to plot behaviours in a linear way. Some approaches could not deal with the diversity of the contexts. Most especially, however, the study highlights that the failure to take account of the underlying theological premise of the FBOs can produce an anomalous picture. The article is cautious about methods which are overt measures of religiosity and favours the quadrant proposed by Vanderwoerd. This approach takes account of the theological outlook of those FBOs that are more comfortable in working with open systems.